2020
DOI: 10.1111/zsc.12418
|View full text |Cite
|
Sign up to set email alerts
|

How many species of angulate tortoises occur in Southern Africa? (Testudines: Testudinidae: Chersina)

Abstract: Using range‐wide sampling and 1,143 bp of mtDNA (cytochrome b gene) and 14 microsatellite loci, we examined genetic differentiation in the widely distributed Southern African angulate tortoise (Chersina angulata). We found evidence for two genealogical lineages that differ in both genetic marker systems and their preferred habitat conditions. According to a fossil‐calibrated molecular clock for all African tortoise lineages using 1,870 bp mitochondrial and 1,416 bp nuclear DNA, the two lineages of C. angulata … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…However, the insular population was not genetically differentiated from the western mainland lineage. In contrast to the deep divergences estimated by Daniels et al (2007), Spitzweg et al (2020) inferred that the two lineages of C. angulata diverged only in the Pliocene (approx. 3.8 million years ago).…”
Section: Phylogeographymentioning
confidence: 63%
See 4 more Smart Citations
“…However, the insular population was not genetically differentiated from the western mainland lineage. In contrast to the deep divergences estimated by Daniels et al (2007), Spitzweg et al (2020) inferred that the two lineages of C. angulata diverged only in the Pliocene (approx. 3.8 million years ago).…”
Section: Phylogeographymentioning
confidence: 63%
“…The phylogeography of Homopus areolatus was studied by Hofmeyr et al (2020) based on range-wide sampling and a 680-bp-long fragment of the mitochondrial ND4 gene combined with evidence from species distribution modeling. Similar to Chersina angulata (Daniels et al 2007;Spitzweg et al 2020) and Pelomedusa galeata (Vamberger et al 2018), two clades were identified, one from the west and the other from the south and east of the range. For the two tortoise species, a small over-lap zone between the clades has been identified (Fig.…”
Section: Phylogeographymentioning
confidence: 90%
See 3 more Smart Citations